PSYCHOMOTRICITY IN EARLY CHILDHOOD EDUCATION: A STATE OF KNOWLEDGE (Fiep Bulletin - online, 2026)
Introduction: Psychomotricity is an area of knowledge that seeks to understand the relationships between the psyche (mind) and motor skills (body). Through it, we seek to understand how movement stimuli enable education to be effective for the integral development of the child and how this process occurs in Early Childhood Education. The objective is to present principles of a State of Knowledge on the influence of Psychomotricity on children's cognitive, affective and motor development, establishing pedagogical bases for its development in Early Childhood Education. Methods: This is a bibliographical research of the State of Knowledge type, through the exploration of databases, pointing out current issues and discussions, synthesis and analysis of concrete experiences of researchers through the results of their research. Results: Regarding the results, 10 texts were selected, produced from 2019 to 2024 and which generated two categories: 1) Affection and the human: foundations for a comprehensive education; and 2) Psychomotricity in education and its contribution to learning through motor, cognitive and affective development; and; 3) The importance of psychomotor activities for stimulating the body and movement. Conclusion: It was concluded that psychomotricity has clear links with the child's learning process and is necessary for the effective development of the child's motor, affective and cognitive development. However, from the perspective of the State of Knowledge, psychomotricity is an area that is currently little explored, but which has quality content and is of great importance for comprehensive education in Early Childhood Education.